Tuning coordination in s-block carbazol-9-yl complexes - Ortu, Fabrizio; Moxey, Graeme J.; Blake, Alexander J.; Lewis, William; Kays, Deborah L. (Wiley-VCH Verlag, 2015)
1,3,6,8-Tetra-tert-butylcarbazol-9-yl and 1,8-diaryl-3,6-di(tert-butyl)carbazol-9-yl ligands have been utilized in the synthesis of potassium and magnesium complexes. The potassium complexes (1,3,6,8-tBu4carb)K(THF)4 (1; carb=C12H4N), [(1,8-Xyl2-3,6-tBu2carb)K(THF)]2 (2; Xyl=3,5-Me2C6H3) and (1,8-Mes2-3,6-tBu2carb)K(THF)2 (3; Mes=2,4,6-Me3C6H2) were reacted with MgI2 to give the Hauser bases 1,3,6,8-tBu4carbMgI(THF)2 (4) and 1,8-Ar2-3,6-tBu2carbMgI(THF) (Ar=Xyl 5, Ar=Mes 6). Structural investigations of the potassium and magnesium derivatives highlight significant differences in the coordination motifs, which depend on the nature of the 1- and 8-substituents: 1,8-di(tert-butyl)-substituted ligands gave π-type compounds (1 and 4), in which the carbazolyl ligand acts as a multi-hapto donor, with the metal cations positioned below the coordination plane in a half-sandwich conformation, whereas the use of 1,8-diaryl substituted ligands gave σ-type complexes (2 and 6). Space-filling diagrams and percent buried volume calculations indicated that aryl-substituted carbazolyl ligands offer a steric cleft better suited to stabilization of low-coordinate magnesium complexes.